Alteration of sFAS and sFAS ligand expression during canine visceral leishmaniosis - Perosso, Juliana [UNESP]; Oliveira Silva, Kathlenn Liezbeth [UNESP]; Souza Ferreira, Stefani Iris de [UNESP]; Avanco, Saulo Vinicius [UNESP]; Patto dos Santos, Paulo Sergio [UNESP]; Eugenio, Flávia de Rezende [UNESP]; Martins de Almeida, Breno Fernando [UNESP]; Felix de Lima, Valeria Marcal [UNESP] (Elsevier B.V., 2014)
Visceral leishmaniosis (VL) is caused by intracellular parasites of the genus Leishmania that affect humans and several animal species. Dogs are one of the main urban reservoirs of Leishmania infantum and play a central role in the transmission cycle to humans via sandflies. CD3+ cells apoptosis is involved in the immune response in VL. Dysregulation of apoptosis has been implicated in various disease states. An important regulator of apoptosis is the FAS-FAS-associated death domain protein (cluster of differentiation 95 - CD95) and FASL-FAS ligand protein (cluster of differentiation 178 - CD178) system involved in the down-regulation of immune reactions and in T cell-mediated cytotoxicity. FAS is a member of the tumor necrosis factor (TNF) receptor super family, which can be expressed in transmembrane or soluble forms. The soluble levels of FAS (sFAS), FASL (sFASL) and active Caspase-3, this last related to apoptotic cascade, were investigated in the spleen of 19 symptomatic dogs presenting moderate VL and 6 healthy dogs, determined by ELISA assay. The splenic parasite load was determined by real-time PCR monitoring of amplification of the intergenic internal transcribed spacer (ITS1) gene of parasite rRNA. sFAS levels were lower (p < 0.05). sFASL and active Caspase-3 levels were higher (p < 0.05)in dogs with VL compared with controls. Negative correlation was observed between parasite burden and sFASL levels. The increase in sFASL could be related to the mechanism involved in the elimination of the parasite. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cell death; FAS-associated death domain protein; FAS ligand protein; Leishmania infantum; Leishmaniosis; TRAIL (TNF-related apoptosis-inducing ligand)